2017
DOI: 10.1590/1983-21252017v30n227rc
|View full text |Cite
|
Sign up to set email alerts
|

Graft Takes of Tomato on Other Solanaceous Plants

Abstract: -This paper aimed to assess tomato grafting on different solanaceous species through two grafting methods. Scions were cut from cultivar Santa Cruz Kada seedlings. A fully randomized experimental design was carried out with treatments in a 9 x 2 factorial scheme. As rootstocks, four accessions of mini-tomatoes (0224-53, RVTC 57, RVTC 20 and 6889-50 -Solanum lycopersicum L); two species of wild tomato (Solanum habrochaites var hirsutum 'PI-127826' and Solanum pennellii 'LA716'); other two tomato species [Solanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
2
5
0
3
Order By: Relevance
“…Studies report that the use of S. habrochaites as rootstock, in comparison with other tomato species, provided an increase in shoot and root dry matter (Zeist, Resende, Giacobbo, Faria, & Dias, 2017) and presented higher values for photosynthetic yield, water use efficiency and fruit production , corroborating this study, where S. habrochaites was an interesting alternative to promote increases in biomass accumulation.…”
Section: Resultssupporting
confidence: 88%
“…Studies report that the use of S. habrochaites as rootstock, in comparison with other tomato species, provided an increase in shoot and root dry matter (Zeist, Resende, Giacobbo, Faria, & Dias, 2017) and presented higher values for photosynthetic yield, water use efficiency and fruit production , corroborating this study, where S. habrochaites was an interesting alternative to promote increases in biomass accumulation.…”
Section: Resultssupporting
confidence: 88%
“…Cleft grafting presented better results at 23/56 and 28/61DAS, respectively, with 50% and 70% success (Figures 2A, 2B). These results were similar to those obtained by Zeist et al (2017), who also observed a higher rate of grafting success when using the combination of this species with the cleft grafting technique.…”
Section: Self-rooted Tomato X Tomato Grafted On Coconasupporting
confidence: 90%
“…Zeist et al (2017) evaluated different grafting methods in different solanaceous species and found that for mini-tomato rootstock 0224-53, RVTC 57 and RVTC 20, as well as wild species S. habrochaites var. hirsutum 'PI-127826', the approach method would be the best.…”
Section: Graft-take Percentagementioning
confidence: 99%